New taxa of Campylomyzini and Pteridomyiini from Tasmania (Diptera: Cecidomyiidae: Micromyinae). - Jaschhof, Mathias; Jaschhof, Catrin (Contributions to Entomology = Beiträge zur Entomologie, 2010)
The following new taxa of Micromyinae are described from Tasmania: Warramyia weldensis Jaschhof gen. et sp. n. (in Campylomyzini); Pteridomyia tasmanica Jaschhof sp. n.; Pseudomonardia dorani Jaschhof sp. n.; Pseudomonardia niklasi Jaschhof sp. n.; Pseudomonardia tobiasi Jaschhof sp. n.; Pseudomonardia dawnae Jaschhof sp. n.; and Hintelmannomyia aestimata Jaschhof gen. et sp. n. (all in Pteridomyiini). Campylomyza grandiuscula Skuse, 1890, which is actually a species of the genus Pteridomyia Jaschhof, 2003, is redescribed on the basis of the holotype and the male terminalia are figured for the first time. A key to the Tasmanian species of Pseudomonardia is provided.KeywordsDiptera, Cecidomyiidae, Micromyinae, Australia, Tasmania, Campylomyzini, Pteridomyiini, new genera, new species.Nomenclatural ActsHintelmannomyia Jaschhof, 2010 (Cecidomyiidae), gen. nov.Warramyia Jaschhof, 2010 (Cecidomyiidae), gen. nov.aestimata Jaschhof, 2010 (Hintelmannomyia), spec. nov.dawnae Jaschhof, 2010 (Pseudomonardia), spec. nov.dorani Jaschhof, 2010 (Pseudomonardia), spec. nov.niklasi Jaschhof, 2010 (Pseudomonardia), spec. nov.tobiasi Jaschhof, 2010 (Pseudomonardia), spec. nov.tasmanica Jaschhof, 2010 (Pteridomyia), spec. nov.weldensis Jaschhof, 2010 (Warramyia), spec. nov.